2006
DOI: 10.2320/matertrans.47.599
|View full text |Cite
|
Sign up to set email alerts
|

The Electronic Structure and Magnetic Properties of Full- and Half-Heusler Alloys

Abstract: The electronic structure of the full-and half-Heusler alloys have been studied by ab-initio calculations using full potential augmented plane-wave-method (FLAPW). It was shown that obtained equilibrium lattice parameters and magnetic moments agree well with available experimental data. The influence of vacancies on the electronic structure and magnetic properties of Ni 2Àx MnGa and Co 2Àx ZrSn is analyzed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(39 citation statements)
references
References 42 publications
(68 reference statements)
6
31
0
2
Order By: Relevance
“…Recently, Li et al investigated theoretically the site preference and elastic properties of Fe-, Coand Cu-doped Ni 2 MnGa alloys by using the first-principles exact muffin-tin orbital method in combination with the coherent-potential approximation [14]. According to the results of the calculation by Li et al [14] [14] are in good agreement with those reported earlier for the stoichiometric Heusler alloy Ni 2 MnGa [15][16][17][18][19][20][21][22]. In order to explain the observed concentration dependence of the magnetic moment for Ni 2 Figure 5 is the one calculated by using this equation.…”
Section: Methodssupporting
confidence: 70%
“…Recently, Li et al investigated theoretically the site preference and elastic properties of Fe-, Coand Cu-doped Ni 2 MnGa alloys by using the first-principles exact muffin-tin orbital method in combination with the coherent-potential approximation [14]. According to the results of the calculation by Li et al [14] [14] are in good agreement with those reported earlier for the stoichiometric Heusler alloy Ni 2 MnGa [15][16][17][18][19][20][21][22]. In order to explain the observed concentration dependence of the magnetic moment for Ni 2 Figure 5 is the one calculated by using this equation.…”
Section: Methodssupporting
confidence: 70%
“…It can be seen that these alloys are ferromagnetic. The results for Cu 2 MnAl compound, which are given in Table I, agree with the experimental results [23,24] and other theoretical works [8,10,11,25]. To the best of our knowledge, no comparable studies in literature on Cu 2 MnSi 1−x Al x (x = 0.125, 0.25, 0.375, 0.5) alloys.…”
Section: Structural Propertiessupporting
confidence: 79%
“…The calculated total and partial spin magnetic moments for Cu 2 MnSi, Cu 2 MnAl and Cu 2 MnSi 1−x Al x quaternary alloy are quoted in Table III [8,11,32,33] and experimental ones [34], which are also reported in Table III. To our knowledge, there are no values of the magnetic moments in the literature for the quaternary alloy.…”
Section: Magnetic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Half-metallic ferromagnets behave as metallic for one electron spin direction and exhibit semiconducting nature in the other spin direction by presenting a gap at Fermi level (E F ). A series of Heusler alloys (NiMnSb, FeMnSb, Mn 2 VGe, Co 2 MnGe, Co 2 CrAl, Fe 2 CrAl, Fe 2 CrSi) have been predicted to be half-metallic ferromagnets [4][5][6][7][8]. Among the full Heusler alloys, Co 2 FeSi exhibits high Curie temperature, high spin polarization at the Fermi level, and a saturation magnetic moment of 6 l B [4].…”
Section: Introductionmentioning
confidence: 97%